2022
DOI: 10.1039/d2na00646d
|View full text |Cite
|
Sign up to set email alerts
|

A rare polyoxometalate cluster [NiW12O44]14−based solid as a pre-catalyst for efficient and long-term oxygen evolution

Abstract: Polyoxometalates (POMs) are an eminent class of metal oxide anionic clusters of early transition metals with huge structural diversity. Herein, a [NiW12O44]14- cluster based solid, (C5H7N2)6 [NiW12O44] has been reported...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…It maintained a current density of 10 mA/ cm 2 for up to 96 h, indicating good stability and outperforming state-ofthe-art RuO 2 electrocatalyst. The observed performance was attributed to the in situ formation of WO x (x = 1,2) and NiO, Ni(OH) 2 , and NiOOH, which act as active phases in the electrocatalyst (Sood et al, 2022).…”
Section: Transition Metal Poms For Oermentioning
confidence: 99%
See 1 more Smart Citation
“…It maintained a current density of 10 mA/ cm 2 for up to 96 h, indicating good stability and outperforming state-ofthe-art RuO 2 electrocatalyst. The observed performance was attributed to the in situ formation of WO x (x = 1,2) and NiO, Ni(OH) 2 , and NiOOH, which act as active phases in the electrocatalyst (Sood et al, 2022).…”
Section: Transition Metal Poms For Oermentioning
confidence: 99%
“…Imani et al designed a Mn-containing POM-based composite that was later deposited onto a rotating carbon paste electrode by two Different hetero-polyoxometalates belonging to the 1:12 series of POMs with various heteroatoms (adapted from Sood et al, 2022).…”
Section: Transition Metal Poms For Oermentioning
confidence: 99%
“…[19][20][21][22] In fact, controversy has arisen on the question of whether POMs are used as true electrocatalysts or only as pre-catalysts. [23][24][25][26][27][28][29][30][31] For OER electrocatalysts, the composition and structure of the catalyst are found to be unstable and the structure of the catalysts undergoes reconstruction to generate new phases that exhibit higher/lower catalytic activity, which suggests that such kinds of catalysts actually act with pre-catalytic effects. In 2022, Parul Sood and co-workers reported a [NiW 12 O 44 ] 14− cluster-based POM (PS-78) and demonstrated that in situ-generated NiO and WO x were active substances for the OER process.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Parul Sood and co-workers reported a [NiW 12 O 44 ] 14− cluster-based POM (PS-78) and demonstrated that in situ-generated NiO and WO x were active substances for the OER process. 31 At present, transition metals such as iron, manganese, and nickel have also emerged as viable alternatives to established OER catalysts. Their catalytic activities are in the order Ni > Co > Fe > Mn, and based on nickel being abundant in the Earth's crust and having excellent electrochemical properties, [32][33][34][35] more attention should be paid to OER research of nickel-based POMs.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs), which are a distinguishing class of nanosized clusters, have recently been proposed as viable water oxidation catalysts (WOCs) because of their strong redox activity, low cost, and high durability. They can also be used as precursors for WOCs for synthesizing nanomaterials, owing to their huge structural diversity. The use of nanomaterials in catalysis has increased significantly in recent years due to higher surface area and more exposed active sites …”
mentioning
confidence: 99%